2021
DOI: 10.1073/pnas.2101498118
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of an anaerobic pathway for metabolism of l -carnitine–derived γ-butyrobetaine to trimethylamine in human gut bacteria

Abstract: Trimethylamine (TMA) is an important gut microbial metabolite strongly associated with human disease. There are prominent gaps in our understanding of how TMA is produced from the essential dietary nutrient l-carnitine, particularly in the anoxic environment of the human gut where oxygen-dependent l-carnitine–metabolizing enzymes are likely inactive. Here, we elucidate the chemical and genetic basis for anaerobic TMA generation from the l-carnitine–derived metabolite γ-butyrobetaine (γbb) by the human gut bact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…On the other hand, l -carnitine is metabolized by gut bacteria and liver to produce TMAO 98 . Nonetheless, the responsible biochemical pathway(s) and required genetic components in gut bacteria to metabolize l -carnitine to TMAO is not yet fully understood 98 , 99 . TMAO was our reference metabolite to assure the germ-free status of the mice used in the study, as it is a metabolite with microbial origin 100 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, l -carnitine is metabolized by gut bacteria and liver to produce TMAO 98 . Nonetheless, the responsible biochemical pathway(s) and required genetic components in gut bacteria to metabolize l -carnitine to TMAO is not yet fully understood 98 , 99 . TMAO was our reference metabolite to assure the germ-free status of the mice used in the study, as it is a metabolite with microbial origin 100 .…”
Section: Discussionmentioning
confidence: 99%
“…6 ). We note that a recent preprint by Rajakovich et al recently identified the same 6-membered gene cluster in E. timonensis in catalyzing TMA generation from γBB 27 . Their independent characterization of the microbial biochemical pathway was highly aligned with our findings, further validating the role of the gbu gene cluster in gut microbial γBB→TMA transformation reported herein.…”
Section: Discussionmentioning
confidence: 57%
“…Although SCFAs derive from dietary fibre, these observations were independent of dietary fibre intake suggesting that other factors may influence the availability of SCFAs. Recent data suggest that SCFAs may derive from the metabolism of l ‐carnitine to trimethylamine, a pathway highlighted by Suzuki at the symposium (Suzuki et al., 2021) and discussed below in relation to the atherogenic phenotype (Rajakovich et al., 2021 ). In their talk, Swann further demonstrated that in contrast to IBS‐C patients, IBS patients with diarrhoea (IBS‐D) present higher levels of tryptophan and its indoleamine microbial metabolite, tryptamine, which again acts locally to regulate intestinal motility by interacting with serotonin receptor‐4 (Swann et al., 2020 ).…”
Section: Microbial Components Cell Signalling and Disease Stratificationmentioning
confidence: 99%
“…The metabolism of choline to TMA seems to involve the direct choline‐TMA lyase pathway (Day‐Walsh et al., 2021 ). However, the metabolism of l ‐carnitine involves the formation of an obligate intermediate, γ‐butyrobetaine, which is further metabolised in a multistep process involving several gene clusters to produce TMA and other metabolites including SCFAs, such as acetate and butyrate, which have been shown to be the end‐products in this process (Day‐Walsh et al., 2021 ; Rajakovich et al., 2021 ). The factors that regulate the formation of TMA from carnitine are yet to be understood although it seems that this pathway may be more important in the production of the atherogenic TMA than that involving choline.…”
Section: Stratifying Disease Outcomes and Clinical Decisions Based On...mentioning
confidence: 99%